Owner power, deliberate strategy formulation, and strategic management accounting - Ari Kuncara Widagdo, Antonius Singgih Setiawan, Rahmawati Rahmawati, Djuminah Djuminah, (Opción, 2019)
This research was conducted to identify the correlation betweenhotel owner power over the strategy formulation preference and theimplementation of strategic management accounting, with theapplication of the sequential mixed-method approach. In the qualitativephase, 11 hotel managers and 2 hotel owners were interviewed. Theresult of the research demonstrates that a no controlling owner powerwill promote deliberate strategy formulation and the implementation ofstrategic management accounting. In conclusion, the preference ofdeliberate strategy formulation will promote the implementation ofstrategic management accounting on a larger scale.